Photocatalytic activity of TiO2-coated glass raschig rings on the degradation of phenolic derivatives under simulated solar light irradiation - Maria J. Sampaio (2013)
Glass raschig rings were coated with different types of TiO2, namely Evonik P25 (EP), anatase TiO2 from Sigma Aldrich (SA), and TiO2 obtained from a sol gel procedure. The efficiency of the coating was tested on the degradation of phenol using simulated solar light irradiation. Regardless the material tested, phenol degradation gradually increases with the number of TiO2 layers. SA-coated glass rings show the highest efficiency for phenol degradation (90% conversion), but do lose activity when reused (78% conversion after 2 cycles) due to particle disaggregation from the support. Rings coated with EP are the most stable with an average 72% conversion over 3 cycles. Raschig rings coated with 3 layers of EP were used for the treatment of a synthetic effluent consisting of a solution with a mixture of seven phenolic derivatives namely phenol, 4-hydroxybenzoic acid, 4-methoxyphenol, 4-phenylethyl alcohol, benzoic acid, protocatechuic acid and gallic acid. Photocatalytic degradation efficiency depended on the organic compound, the most easily degraded molecule being gallic acid (85% removal after 8 h of irradiation) contrasting with 4-hydroxybenzoic acid which was the most refractory compound (3% removal). A relationship between the extent of photocatalytic degradation and the activating/deactivating nature of the aromatic ring substituents is proposed.